PENGELOLAAN HASIL BELAJAR DAN SIKAP KRITIS SISWA PADA MATERI KEMERDEKAAN MENGEMUKAKAN PENDAPAT DENGAN BERITA DARI TELEVISI SEBAGAI MEDIA PEMBELAJARAN - Lasih Lasih (UNIVERSITAS BENGKULU, 2017)
The purpose of this research to know management of critical attitudes and study result of subjects Citizenship with the news media on the television. The subject of this research is fouth grade 7th in SMP N 13 Lubuklinggau. Based on the results of the assessment process and analysis of daily tests, it can be concluded that an increase of 21.93% a critical attitude, and study result in the form of individual completeness average by 6.35% and amounted to 44.74% classical completeness of pre cycle to first cycle. While from first cycle to second cycle increased the critical attitude of learning by 50.88%, individual mastery at 2.00% and amounted to 13.16% classical completeness. The author suggested to the teachers to use the news media of television according to its competence expected.